Higher mortality in stroke patients with active COVID-19 infection - Mostafa Almasi-Dooghaee; Seyedehnarges Tabatabaee; Fatemeh Moghadas; Tara Khoeini; Mona Ramezani Ghamsari; Tayebeh Lotfi; Matineh Heidari; Zakieh Shafiei; Roya Yazdani; Zahra Mirzaasgari; Seyed Mohammad Tabatabaei; Mehdi Moghaddasi; et al. (Exploration of Neuroprotective Therapy, 2025)
Aim: Our previous research (Abstract, J Vessels Circ. 2021;2) suggested an increased risk of thrombotic events, including ischemic strokes, in patients with COVID-19. This study aims to determine the mortality rate and its predictors in patients with stroke and concurrent COVID-19 infection. Methods: A retrospective analysis was conducted on stroke patients admitted to three Iranian referral hospitals within a 3-month period during the COVID-19 pandemic (COV-pos and COV-neg groups). The mortality rate was compared to a similar period one year before the pandemic (non-COV group). The Cox proportional hazards model was used to assess the independent and interactive effects of various variables on mortality. Results: Among 124 stroke admissions, 59 (47.6%) had confirmed COVID-19 infection. The COV-pos group had a significantly higher initial NIHSS score (P = 0.001) compared to other groups. Mortality rates were 49.2%, 24.2%, and 17.3% in the COV-pos, COV-neg, and non-COV groups, respectively (P < 0.001). Posterior cerebral artery (PCA) stroke (HR = 65.099), internal carotid artery (ICA) stroke (HR = 19.102), and a history of diabetes mellitus (HR = 3.824) were identified as the most significant predictors of mortality in patients with stroke and COVID-19 infection. Conclusions: Stroke patients with COVID-19 infection exhibited a significantly higher mortality rate compared to patients without COVID-19. The type of stroke involving the PCA or ICA and a history of diabetes emerged as the strongest predictors of mortality in the studied population.